University and the Narrative of Ethno-Religious Relations in West Kalimantan - Yusriadi Yusriadi; Munawar Munawar; Huzaimah Agustini; Imron Muttaqin; Mujiono Mujiono; Fahmi Ichwan (Al-Hayat Al-Istiqomah Foundation collab with Letiges, 2023)
The purpose of this study is to describe and analyze educational institutions' contribution to the study of Islam and ethnicity in West Kalimantan and to see the relationship between the two. The method used is qualitative, with a literature study approach and documentation of published or published materials. Data analysis by classifying thematically and qualitative description. Testing the validity of the data was carried out using triangulation. The analysis results concluded that educational institutions in West Kalimantan had significantly contributed to building ethnoreligious narratives in West Kalimantan. Through lecturers and students, educational institutions such as IAIN Pontianak, Tanjungpura University Pontianak, IAIN Sambas, Pontianak State Polytechnic have conducted studies on Islam and ethnicity. In particular, studies on Islam and Malay, Islam and Dayak, Islam and China (Chinese), Islam and Madura, and Islam and Bugis are carried out by lecturers and students studying in educational institutions and society. These studies also strengthen the ethnoreligious narrative that Islam is an inessential part of theconstructinghnic communities in West Kalimantan. The systematic research design presents important social engineering material for the future of religious and ethnic relations, especially Islam and ethnicity in this area.